2016
DOI: 10.1021/acs.jpcc.6b08593
|View full text |Cite
|
Sign up to set email alerts
|

Aluminum and Gallium Substitution in Yttrium and Lutetium Aluminum–Gallium Garnets: Investigation by Single-Crystal NMR and TSL Methods

Abstract: The work reports the results on 71 Ga and 27 Al NMR investigation of the gallium and aluminum ions distribution over tetrahedral and octahedral positions in the Y 3 Al 5−x Ga x O 12 :Ce single crystals and Lu 3 Al 5−x Ga x O 12 :Ce single-crystalline epitaxial films. The gallium content x varies between 0 and 5 in crystals and between 0.3 and 2 in films.. We find that in both the Y-and Lu-based solid solutions the larger gallium ions are preferably located at the tetrahedral position while the smaller aluminum… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1
1

Citation Types

2
36
0

Year Published

2017
2017
2023
2023

Publication Types

Select...
7

Relationship

1
6

Authors

Journals

citations
Cited by 53 publications
(38 citation statements)
references
References 47 publications
(113 reference statements)
2
36
0
Order By: Relevance
“…By the analogy with LGSO:Ce, in the garnet structure of YAGG:Ce the tetrahedral and octahedral sites are enriched with Ga 3+ and Al 3+ , correspondingly. This was proved by the NMR analysis based on determination of 27 Al, 71 Ga, and 69 Ga isotope concentrations . Ga 3+ ions preferably occupy the tetrahedral sites, while Al 3+ ions preferably occupy the octahedral sites.…”
Section: Causes Of Clusterization In Mixed Crystalsmentioning
confidence: 90%
“…By the analogy with LGSO:Ce, in the garnet structure of YAGG:Ce the tetrahedral and octahedral sites are enriched with Ga 3+ and Al 3+ , correspondingly. This was proved by the NMR analysis based on determination of 27 Al, 71 Ga, and 69 Ga isotope concentrations . Ga 3+ ions preferably occupy the tetrahedral sites, while Al 3+ ions preferably occupy the octahedral sites.…”
Section: Causes Of Clusterization In Mixed Crystalsmentioning
confidence: 90%
“…The latter can appear due to the fluctuations of the the bottom of the conduction band appearing in mixed solid solutions 41,42 and distortion of the vacuum levels of the defects due to statistical variation of the cations distribution in the second coordination sphere around the defect. 19,43 In the Fig. 6 fluctuations of the bottom of the conduction band and energy level of the defects are schematically shown by two bell shaped curves.…”
Section: Signs Of Trap Depth Distributionmentioning
confidence: 99%
“…The decay time sharply drops between the samples with 40 and 60% Ga, though the common trend of decay time decrease with Ga concentration is clear. Recently 21 , it was shown that Ga 3+ Please do not adjust margins Please do not adjust margins preferably occupies the tetrahedral sites in YAGG (though larger Ga 3+ atoms was supposed to occupy first the larger octahedral sites). The interval between 40 and 60 % of Ga corresponds to the situation when the number of Ga atoms exceeds the number of Al atoms and Al 3+ /Ga 3+ substitution into octahedral sites starts.…”
Section: Decay Time and Phosphorescencementioning
confidence: 99%